Investigating the Effect of the Routine Physical Therapy with and without Reflexology on the Level of Pain, Disability and Endurance of the Trunk Extensor and Flexor Muscles in Subjects with Chronic Nonspecific Low Back Pain - Mikaili, Saeed; Jahantigh Akbari, Narges (Journal of Clinical Physiotherapy Research, 2019)
Introduction: low back pain is one of the most common and expensive musculoskeletal disorders which due to its disability, the health care system is faced with great problems such as social and remedial ones. Different methods are used in order to alleviate the pain .one of the most common way to alleviate the complications of the low back pain is the foot reflexology. The aim of this study is to investigate the effect of adding this kind of treatment as an inexpensive nonaggressive way to the routine physical therapy plan. Methods and Materials: In this quasi experimental study, 30 women with chronic nonspecific low back pain returnee to physiotherapy clinic in Tehran, first were selected by purposive sampling then they with random allocation method had been divided to two groups: routine physiotherapy (electrotherapy and strength training of flexor and extensor muscles) and routine physiotherapy plus foot reflexology. The amount of pain and functional disability and flexor and extensor endurance were measured by VAS and Oswestry disability questionnaire and ITOO test before, just after 8 weeks treatment and with a month interval after intervention. Data were analyzed using repeated measure ANOVA. The statistical significance was resumed to be a P<0.05. Results: Before intervention anthropometric, quantitative, and qualitative specifications were not significantly different between two patients groups participating in this study. Immediately after completing their physiotherapy treatment plan, although the pain and disability reduction were seen in both groups, the reflexology group was better than routine physiotherapy (P<0.05), Endurance of trunk muscles was not significantly different in both groups. A month after the final physiotherapy session, the pain, disability and endurance were not significantly different between two groups (P>0.05). Conclusion: Adding reflexology to the treatment plan had a positive effect only for a short term in improving the pain and disability, but in long term, applying reflexology besides the routine physiotherapy treatment had no additional effect and the routine results were established. Future studies with more subjects and in acute low back pain is recommended.